Effect of vaccination against yersiniosis on the relative percent survival, bactericidal and lysozyme response of Atlantic salmon, Salmo salar - Costa, AA; Melanie Leef; Andrew Bridle; Carson, J; Barbara Nowak (2011)
The bacterium Yersinia ruckeri serovar O1b causes yersiniosis in Atlantic salmon, Salmo salar , in the southern hemisphere. Despite vaccination this disease has resulted in significant hatchery losses in the Tasmanian Atlantic salmon aquaculture industry. A poor response to vaccination in juveniles, 1–5 g, has lead to the investigation of the suitability of the current formalin killed whole-cell vaccine Yersinivac-B. In this study trypsin was added to the Yersinivac-B to expose the bacteria's protective O-antigen to make the vaccine more immunogenic. At six weeks post vaccination, the effect of Yersinivac-B and the novel trypsinated Yersinivac-B vaccine on body mucus lysozyme and mucus and serum bactericidal activity of fish was determined over a 48 h period following challenge with Y. ruckeri . Body and gill mucus lysozyme and mucus and serum bactericidal activity was also determined in surviving fish at 10 weeks post Y. ruckeri challenge. Following the challenge period of 14 days the trypsinated Yersinivac-B fish demonstrated a significantly higher percent survival compared to the Yersinivac-B and control unvaccinated fish. Body mucus lysozyme concentration was also significantly elevated at 8 h post challenge in the trypsinated Yersinivac-B fish compared to controls. This variable however appears unlikely to play a significant role in protection as positive bactericidal activity was not found in the mucus of any fish following challenge. Bactericidal activity was not observed in the serum or mucus of any challenge survivors. At 8 h post challenge the trypsinated Yersinivac-B fish demonstrated the highest serum bactericidal activity. However, the unvaccinated control fish also displayed positive serum bactericidal activity despite being unlikely to have been previously exposed to Y. ruckeri . A significantly higher gill mucus lysozyme concentration in control survivors compared to vaccinated fish suggests that this response may be important in the protection of unvaccinated fish against yersiniosis. This ...